Perancangan Media Video Komunikasi Visual Instagram Reels Narasi - Yani, Aditya Rahman; Santoso, Bilgies Diva; Wardani, Nuril Kusuma (Jurnal Ilmiah Wahana Pendidikan, 2024)
Media is providing information by adding text or repeating visual presentations to engage the audience. The use of images in visual media helps differentiate two different concepts. One of the projects being worked on is the Visual Video Media project for Instagram Reels. By knowing Instagram, the aim is to find out how the system is implemented. This research method uses the data collection stage through research on social media and the latest news, the design stage starting from Pre-Production, Production, to Post-Production. There are several choices of visual concepts that will influence a visual that will be uploaded to Instagram Reels, namely, typography/typeface, paper visual effects which are characteristic of Better Youth, and even size format rules for Instagram Reels itself. The narrative news design process consists of receiving a brief in the form of a Content Planner, analyzing the brief, searching for data and visual assets, and creating a concept. Then design the oral news into a Visual Narrative News and process it using Adobe Premiere Pro, After Effects, and Illustrator. The final process, narrative news is created in the form of Instagram Reels.